2009
DOI: 10.1158/1078-0432.ccr-08-1867
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Neoadjuvant Imatinib in Glioblastoma: Evaluation of Clinical and Molecular Effects of the Treatment

Abstract: Purpose: Phase I-II studies indicate that imatinib is active in glioblastoma multiforme.To better understand the molecular and clinical effects of imatinib in glioblastoma multiforme, we conducted a neoadjuvant study of imatinib with pretreatment and posttreatment biopsies. Experimental Design: Patients underwent a computerized tomography-guided biopsy of their brain tumors. If diagnosed with glioblastoma multiforme, they were immediately treated with 7 days of imatinib 400 mg orally twice daily followed by ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 31 publications
1
57
0
4
Order By: Relevance
“…Imatinib mesylate (Gleevec ® , Novartis) was developed to specifically inhibit Bcr-Abl signal transduction in chronic myeloid leukemia, and was later shown to also inhibit c-Kit and platelet-derived growth factor receptor (PDGFR) activity. The latter finding supported clinical testing of imatinib for GBM treatment, and similarly to the EGFR inhibitors, response rates were variable but promising (Razis et al, 2009;Wen et al, 2006). Other targeted therapy compounds currently evaluated for use in GBM treatment are described in section 5.…”
Section: Standard Of Care and Other Therapeutic Optionsmentioning
confidence: 72%
“…Imatinib mesylate (Gleevec ® , Novartis) was developed to specifically inhibit Bcr-Abl signal transduction in chronic myeloid leukemia, and was later shown to also inhibit c-Kit and platelet-derived growth factor receptor (PDGFR) activity. The latter finding supported clinical testing of imatinib for GBM treatment, and similarly to the EGFR inhibitors, response rates were variable but promising (Razis et al, 2009;Wen et al, 2006). Other targeted therapy compounds currently evaluated for use in GBM treatment are described in section 5.…”
Section: Standard Of Care and Other Therapeutic Optionsmentioning
confidence: 72%
“…Upon activation, GDP is replaced by guanosine triphosphate (GTP), resulting in subunit dissociation into a βγ dimer and the GTP-bound α-monomer (67). The Ga subunit is classified into four families: Ga s , Ga i , Ga q and Ga 12 . Each Ga family can transmit different downstream signals, thereby affecting diverse biological functions (68).…”
Section: Gpcr Blockers In Cancermentioning
confidence: 99%
“…The first-generation small-molecule EGFR inhibitors, such as gefitinib, have performed poorly against GBM in several clinical trials (8)(9)(10). While the Bcr-Abl-targeting drug imatinib revealed notable efficacy for patients with chronic myeloid leukemia, clinical trials of imatinib in GBM have failed to demonstrate any therapeutic advantages (11)(12)(13). Finally, dasatinib, a platelet-derived growth factor and Src inhibitor failed to show benefit in recurrent GBM patients, either alone or in combination with bevacizumab (14).…”
Section: Introductionmentioning
confidence: 99%
“…In another experimental study, imatinib significantly inhibited the proliferation of human U87 glioblastoma cells and significantly increased the radiosensitivity of this glioma cell line in vitro and in vivo (Oertel et al, 2006). However, in clinical phase I and II trials, imatinib was shown to exert only moderate antitumor activity (Razis et al, 2009;Wen et al, 2006). In a phase I/II study, 34 patients with glioblastoma were treated with imatinib monotherapy at a dose of 800 mg/d .…”
Section: Inhibitors Of Kitmentioning
confidence: 99%
“…In a different phase II study, 20 patients with glioblastoma were diagnosed by tumor biopsy and treated with 400 mg imatinib administered twice a day for a period of 7 days prior to re-biopsy or tumor resection. Molecular examination of the tumor specimens showed that treatment with imatinib did not significantly change Ki67 expression, suggesting that treatment with imatinib did not affect tumor proliferation (Razis et al, 2009). …”
Section: Inhibitors Of Kitmentioning
confidence: 99%